Perancangan Sistem Informasi Retensi Rekam Medis Pasien Rawat Jalan di Rumah Sakit Umum Proklamasi Karawang - Salma Riyadhul Jannah; Dina Sonia; Falaah Abdussalaam (Syntax Corporation Indonesia, 2021)
The hospital is a health service facility that organizes public health efforts. In carrying out its duties, the hospital records and reports patient health. Recording and reporting of patients can be seen from the medical record file. After the storage time limit is exceeded, the medical record can be retained or destroyed. Medical record retention is an activity to separate active and inactive medical records which aims to reduce the burden of storage racks. This study aims to design an outpatient medical record retention information system using Microsoft Visual Studio 2010 at the Proklamasi Hospital Karawang. Based on the research conducted, a problem was found, namely the retention system is still manual and not fully computerized, by sorting the medical record files one by one to separate between active and inactive files resulting in a long process. So it is necessary to have a retention information system to accelerate the destruction of medical record files. The design method uses the waterfall method. The method stages are Planning, Analysis, Design, Implementation, maintenance. The medical record retention information system that has been created, it can be concluded that the system can facilitate officers in carrying out medical record file destruction activities to be more effective and efficient.